2009
DOI: 10.1002/ijc.24070
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of proteinase‐activated receptor 4 promotes colon cancer cell proliferation through a persistent signaling that involves Src and ErbB‐2 kinase

Abstract: Thrombin is now recognized as an important factor in many cancers. Here, we examined the expression and role of the recently discovered thrombin receptor PAR4, in human colon cancer cells. PAR4 mRNA was found in 10 out of 14 (71%) human colon cancer cell lines tested but not in epithelial cells isolated from normal human colon. This finding is in line with immunostaining results of PAR4 in human colon tumors and its absence in normal human colonic mucosa. Investigation of the functional significance of the abe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…The expression of PAR1 has been correlated with the malignant phenotype. For PAR1, a role in the progression of epithelial tumors, including breast (75,82,94,97,98), colon (76,99), kidney (100), pulmonary tumor (101), melanoma (102) and hepatocellular carcinoma (80,103) has been shown.…”
Section: Action Of Par-mediated Thrombin In Tumorigenesismentioning
confidence: 99%
“…The expression of PAR1 has been correlated with the malignant phenotype. For PAR1, a role in the progression of epithelial tumors, including breast (75,82,94,97,98), colon (76,99), kidney (100), pulmonary tumor (101), melanoma (102) and hepatocellular carcinoma (80,103) has been shown.…”
Section: Action Of Par-mediated Thrombin In Tumorigenesismentioning
confidence: 99%
“…Indeed, we previously demonstrated that in colonic tumors, trypsin acting through up-regulated PAR-2 and thrombin acting through aberrantly expressed PAR-1 and PAR-4 are very robust growth factors that control mitogen-activating protein kinase (MAPK) activation and subsequent cell proliferation and migration of human colon cancer cells. 8,[11][12][13] Furthermore, PARs participate in cell invasion and metastasis of many cancers. 7,14,15 However, despite an intense research to discover novel PAR activators, 4,5,16 -18 the endogenous enzymes responsible for activating PARs in colon cancer remain unknown.…”
mentioning
confidence: 99%
“…Positive expression of PAR4 in some tumors have been found in previous studies and is thought to be involved in hepatocellular carcinoma cell migration and colon cancer progression (Kaufmann et al, 2007;Gratio et al, 2009). It was also reported that PAR4 activation contributed to the hematogenous metastasis of melanoma using the knockout mice (Camerer et al, 2004).…”
Section: Discussionmentioning
confidence: 74%